Concept-level sentiment analysis in the manufacturing industry - Teng, He Xu (Nanyang Technological University, 2020)
The rapid evolution in the field of artificial intelligence (AI) have produced huge impacts on human society, business and industries. AI has been described as the key for the industrial revolution 4.0, in which many of the industrial companies has begun to adopt this powerful technology in pursuit of efficiency and productivity. As one of the subfields of AI, sentiment analysis has been raising its attention in the industrial field. Sentiment analysis is the process of determining the opinion about a given subject from written or spoken language.